Postoperative legal disputes involving patients with cochlear implants - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: After the implantation of one or two cochlear implants additional problems often arise concerning the question which further costs have to be covered by statutory insurances or other insurance providers, e.g. within the framework of integration aid. OBJECTIVE: This article provides an overview of judgments rendered by the German social courts. It was investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIAL AND METHODS: A search was made for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear", "Cochlea", "Implant", and "Implantat". The reviewed judgments were issued between 2002 and 2017. RESULTS: A total of 13 judgments were found. The results varied according to the specifics of the individual case and 54% of the patients won their cases. The court procedures took between 2 months (starting from the filing of a complaint, date of application in this case unknown), and 6 years and 11 months. CONCLUSION: This study showed that it is uncertain whether costs that are not caused directly by the surgery or the postoperative treatment will be remunerated. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory insurances or other providers refuse to meet expenses incurred.
EVALuna2:35385